2019
DOI: 10.4049/immunohorizons.1900074
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of MHC Class I Processing Pathways That Generate a Response to Vaccinia Virus Late Proteins

Abstract: Use of recombinant viral vectors encoding nonnative Ags is an attractive mechanism for the generation of protective Ab, CD4 + T cell (T CD4+ ), and CD8 + T cell (T CD8+ ) responses in vivo following immunization. However, the life cycle and tropism of the viral vector, and its interactions with various components of the immune system, must be fully understood to maximize the efficacy of any vaccination strategies. Ab and T CD4+ responses typically target native Ags driven by late promoters in vaccinia virus (V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 72 publications
(168 reference statements)
1
4
0
Order By: Relevance
“…Together, these findings suggest that L2 53 elicits CD8 + T cells by cross priming, and this is why the CPXV inhibitors fail to reduce L2 53 -specific responses. These two examples support the evidence from others that priming pathway can differ among antigens, epitopes, and constructs for orthopoxviruses, even if direct priming is most consistently observed ( 8 , 13 , 47 50 ). Further, some studies suggest that direct and cross presentation pathways can be utilized sequentially in the priming of epitopes ( 48 , 51 ).…”
Section: Discussionsupporting
confidence: 86%
“…Together, these findings suggest that L2 53 elicits CD8 + T cells by cross priming, and this is why the CPXV inhibitors fail to reduce L2 53 -specific responses. These two examples support the evidence from others that priming pathway can differ among antigens, epitopes, and constructs for orthopoxviruses, even if direct priming is most consistently observed ( 8 , 13 , 47 50 ). Further, some studies suggest that direct and cross presentation pathways can be utilized sequentially in the priming of epitopes ( 48 , 51 ).…”
Section: Discussionsupporting
confidence: 86%
“…As a consequence late viral antigens such as A19 or D13 induce low CD8 + T cell responses, not only because of a delayed expression kinetic in infected cells, but also due to the detention of late antigens in viral factories ( Figure 4A) (50). Likewise, late antigens showed a reduced availability for cross-presentation by antigen presenting cells during infection ( Figures 4B,C) (50,60,61). On the other hand, our in vivo data correlate with the results obtained from the phenotypical analysis of BMDC maturation (Figure 7).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to CD8 + T cells, CD4 + T cells are also important for controlling VACV infection; however, results differ based on the route of viral inoculation. Moutaftsi et al demonstrated that VACV-specific CD4 + T cells recognize determinants from different viral proteins compared to CD8 + T cells, including viral structural and regulatory proteins expressed at later stages of VACV infection [47,48]. These findings are consistent with a role for cross-presentation during CD4 + T cell activation after the transfer of late VACV proteins to APCs [49].…”
Section: T Cell Recruitment To the Skin And Cytotoxic Activitymentioning
confidence: 81%